Cost-effectiveness analysis of mammography screening for early detection of breast cancer in Nigeria - Ifeoma Jovita Nduka; Charles Ebuka Okafor; Obinna Ikechukwu Ekwunife (PLoS ONE, 2026)
Mammography still remains the gold standard for breast cancer screening, considering its impact on breast cancer mortality. However, it has a relatively low utilization rate in Nigeria. Although the National Strategic Cancer Control Plan (NSCCP) has a goal of making screening services and early detection of cancer available for all Nigerians, there is currently no national breast cancer screening program implemented in Nigeria. The modelling study aimed to evaluate the cost-effectiveness of mammography screening from the healthcare provider’s perspective and to determine the appropriate screening interval for Nigerian women, aiming to enhance the efficiency and effectiveness of breast cancer detection programs. A state-transition Markov model was adapted to simulate annual and biennial mammography, breast cancer diagnosis, and treatment in a cohort of cancer-free Nigerian women aged 40 years and followed them for a lifetime. The study was conducted from the healthcare provider’s perspective. Disability-adjusted life year (DALY) averted, representing the health outcomes, was used to estimate the incremental cost-effectiveness ratio (ICER). Costs and outcomes were discounted at an annual rate of 5%. Annual mammography screening costs US$238.60, averted a DALY of 1.060, and was the most cost-effective intervention with an ICER of US$207.24 (95% CI US$213.31 – US$216.88)/DALY averted, which was below the willingness-to-pay threshold of $1074. Mammography screening strategies were estimated to be cost-effective from the healthcare payer’s perspective under the model assumptions. Annual screening showed the most favorable cost-effectiveness profile among the strategies evaluated, but this finding is model-dependent and should be interpreted as comparative economic evidence rather than a definitive screening recommendation. These results can inform future research, policy discussions, and consideration of sustainable financing for breast cancer screening in Nigeria.